(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
There are as many as 52 statutory towns in the NCR-Haryana sub-region as per 2011 census. Out of these, thirteen are Class – I cities that have experienced frequent revision in their administrative limits. The proximity and excellent connectivity to the National Capital explains the spatial expansion in territorial jurisdiction of many of these cities. Sonipat, a Class-I city of NCR-Haryana is one such example. The rapid urban-industrial development of Sonipat that experienced extension of municipal limits four times during 1961-2011 was explained by its close proximity to Delhi. Establishment of industries, development of infrastructural facilities and coming up of new administrative, educational and trade activities created new employment opportunities and attraction for urban living which resulted in large scale influx of migrants. The present paper attempts to meaningfully analyze the spatial growth of Sonipat city to understand its transformation from a small town to an important multifunctional urban centre of Haryana. The study is based on census data from 1961-2011 and urban land use data from 1961-2015.